Analisa Penggunaan Recloser Untuk Pengaman Arus Lebih Pada Jaringan Distribusi 20 kv Gardu Induk Garuda Sakti - Ario Putra; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PT.PLN: 20 kV network substations Garuda Sakti, frequently interference, one of interferences is the short-circuit current. To install equipment to include Recloser. This paper discuss the analysisof the use Recloser on distribution network 20 kV, this paper also be simulated using the software ETAP 12.6 which will feature some of the parameters for comparison of calculations and data thatalready exists in PLN, with two parameters, short circuit and coordination Recloser with overcurrent relay (OCR). Recloser is supposed to work first on feeder interferences and OCR on theincoming side works for incoming 20 kV interferences.Keywords: Recloser, relay overcurrent, short circuit and simulation ETAP 12.6